Pre-operative and post-operative audiological evaluation of type 1 tympanoplasty and comparison between temporalis fascia graft and tragal perichondrium graft - Singh, Satguru Saran; Parmar, Sandip M.; Sood, Abhey; Saroha, Nilank; Chaudhary, Meenu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Aim of the study was to evaluate the hearing improvement of type 1 tympanoplasty performed by using autologous temporalis fascia and autologous tragal perichondrium graft in successfully operated and graft uptake cases, with respect to age, sex, size of perforation and type of graft. Methods: This prospective study consists of total 100 patients with chronic suppurative otitis media (CSOM) tubotympanic disease who have undergone type 1 tympanoplasty. Randomization of patients was done. Every alternate patient was divided accordingly in to two groups-one in temporalis fascia graft group and another in tragal perichondrium graft group. Pure tone audiometry (PTA) was performed preoperatively and 3 months after surgery. Cases with successful graft uptake were included in the study. Statistical comparisons were performed using the t test, and ANOVA test. Results: In this study maximum numbers of patients were found in the age group of 15-30 years. Study showed that audiological benefits were more in males in comparison to females. Large size of perforation showed more improvement due to more air bone gap in comparison to medium size and small size perforation of ears. Audiological improvement occurred in 94% of cases, 3% cases worsened and 3% cases showed no change. More improvement was found in temporalis fascia graft in comparison to tragal perichondrium graft. Conclusions: Type 1 tympanoplasty is a safe and effective technique to improve the quality of life of patients. Size of perforation, type of graft was found to have a major effect on the final outcome of surgery.